Investigating Nanoscale Electron Transfer Processes at the Cell-Mineral Interface in Cobalt-Doped Ferrihydrite Using Geobacter sulfurreducens: A Multi-Technique Approach - Buchanan, Dawn M.; Newsome, Laura; Lloyd, Jonathan R.; Kazemian, Majid; Kaulich, Burkhard; Araki, Tohru; Bagshaw, Heath; Waters, John; van der Laan, Gerrit; N’Diaye, Alpha; Coker, Victoria S. (Frontiers in Earth Science, 2022)
Cobalt is an essential element for life and plays a crucial role in supporting the drive to clean energy, due to its importance in rechargeable batteries. Co is often associated with Fe in the environment, but the fate of Co in Fe-rich biogeochemically-active environments is poorly understood. To address this, synchrotron-based scanning X-ray microscopy (SXM) was used investigate the behaviour of cobalt at the nanoscale in Co-Fe(III)-oxyhydroxides undergoing microbial reduction. SXM can assess spatial changes in metal speciation and organic compounds helping to elucidate the electron transfer processes occurring at the cell-mineral interface and inform on the fate of cobalt in redox horizons. G. sulfurreducens was used to reduce synthetic Co-ferrihydrite as an analogue of natural cobalt-iron-oxides. Magnetite [Fe(II)/Fe(III)3O4] production was confirmed by powder X-ray diffraction (XRD), SXM and X-ray magnetic circular dichroism (XMCD) data, where best fits of the latter suggested Co-bearing magnetite. Macro scale XAS techniques suggested Co(III) reduction occurred and complementary SXM at the nanoscale, coupled with imaging, found localised biogenic Co(III) reduction at the cell-mineral interface via direct contact with outer membrane cytochromes. No discernible localised changes in Fe speciation were detected in the reordered cobalt-iron-oxides that were formed and at the end point of the experiment only 11% Co and 1.5% Fe had been solubilised. The solid phase retention, alongside the highly localised and preferential cobalt bioreduction observed at the nanoscale is consistent with retention of Co in redox zones. This work improves our fundamental molecular-scale understanding of the fate of Co in complex environmental systems and supports the development of biogenic Co-doped magnetite for industrial applications from drug delivery systems to magnetic recording media.